Comparative Computational Analysis of Dirithromycin and Azithromycin in Search for a Potent Drug against COVID-19 caused by SARS-CoV-2: Evidence from molecular docking and dynamic simulation - Adel, Kadri; Amor, Mosbah; Alaeddine, Redissi; Emira, Noumi; Mousa, Alreshidi; Kaïss, Aouadi; Siwar, Ghannay; Jamal, Siddiqui Arif; Mohd, Adnan; De Feo, Vincenzo; Mejdi, Snoussi (Cellular and Molecular Biology, 2022)
Due to the emergency and uncontrolled situation caused by the COVID-19 pandemic that arising in the entire world, it is necessary to choose available drugs that can inhibit or prevent the disease. Therefore, the repurposing of the commercial antibiotic, dirithromycin has been screened for the first time against fifteen receptors and compared to the azithromycin using a molecular docking approach to identify possible SARS-CoV-2 inhibitors. Our docking results showed that dirithromycin fit significantly in the Furin catalytic pocket having the lowest binding score (-9.9 Kcal/mol) with respect to azithromycin (-9.4 Kcal/mol) and can interact and block both Asp154 and Ser368 residues by Van der Walls interaction as well as bound to His194 and Ser368 residues via hydrogen bonds. Good results were also obtained with the Tmprss-2 receptor. A Molecular Dynamic simulation was assessed to confirm this interaction. Additionally, detailed receptor-ligand interactions with SARS-CoV-2 and pro-inflammatory mediators were investigated suggesting more target information with interesting results. The findings of this study are very efficient and provide a basis for the development of dirithromycin for clinical trial applications to be efficient in treating SARS-CoV-2 infections.